Detection of microscope-excited surface plasmon polaritons with Rayleigh scattering from metal nanoparticles - Du, Luping (2014)
We propose a mapping tool of surface plasmon polaritons (SPPs) excited using an optical microscope. By combining dark-field and confocal microscopy, we can efficiently extract metal nanoparticle-induced Rayleigh scattering from background radiation, thereby leading to state-of-the-art SPP measurements. The method is verified to be sensitive to the dominant perpendicular field component of SPPs and be of high accuracy. We also use this method to reveal the conversion of spin angular momentum of light to the orbital angular momentum of SPPs under tight-focusing conditions.